Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Sumber Rezeki Bersama Melalui Semangat Kerja Sebagai Variabel Intervening - Huatauruk, Rapat Piter Sony; Zalukhu, Rika Surianto (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2024)
This study aims to examine the effect of the work environment on employee performance through work morale as an intervening variable. The research employs a quantitative method and was conducted on 43 marketing employees of PT. Sumber Rezeki Bersama. The sampling technique used was saturated sampling. Primary data were collected using questionnaires, and respondents' perceptions were measured using a Likert scale. Data analysis was performed using the path analysis method. The results indicate that the work environment has a positive and significant effect on work morale at PT. Sumber Rezeki Bersama. However, the work environment has a negative and insignificant effect on employee performance. Furthermore, work morale has a positive and significant effect on employee performance and mediates the relationship between the work environment and employee performance at PT. Sumber Rezeki Bersama. The direct implication of this study is that the management of PT. Sumber Rezeki Bersama should create a conducive work environment to enhance work morale, as work morale has been proven to mediate the effect of the work environment on employee performance.